High-binding-force diamond-like coating and preparation method thereof
By setting the Cr base layer and multi-layer composite coating on the stainless steel substrate layer, the problem of high stress and easy peeling of the DLC coating is solved, and a coating with high binding force and wear resistance is achieved, which extends the service life.
Patent Information
- Application Number
- CN202411963104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Due to structural denseness and uniformity problems, DLC coatings lead to high stress and easy peeling, which affects its service life.
A Cr base layer is provided on the stainless steel substrate layer and one or more composite coatings are added thereto, including ZrxAlyCuzNiq coating, bonding layer and DLC coating. Through the design of intermetallic compounds and bonding layers, the binding force of the coating to the substrate is enhanced and internal stress is relieved.
It significantly improves the binding force between the DLC coating and the substrate, reduces internal stress, extends the service life of the coating, and optimizes the wear resistance, avoids cracking, layering and peeling of the coating.
Smart Images

Figure BDA0005217664500000101 
Figure BDA0005217664500000111 
Figure BDA0005217664500000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface coating processing, and in particular relates to a high-bonding force diamond-like coating and a preparation method thereof. Technical Background
[0002] Diamond-like carbon (DLC) coatings are often used in many fields such as mechanical parts (such as tools, bearings, piston rings), electronic devices (such as semiconductors and MEMS devices), medical devices (such as scalpels and implants), and coating protection in the automotive and aerospace fields due to their excellent hardness, low friction coefficient, good wear resistance and chemical stability. However, since the structure of DLC coatings is usually composed of carbon atoms in the form of sp 3 and sp 2 This unique atomic arrangement may affect the density and uniformity of the coating, thereby generating higher stress inside the coating. At the same time, the unevenness that may exist in the deposition process and the different materials of the substrate and the DLC coating further reduce the bonding ability between the DLC coating and the substrate, causing the coating to easily crack and peel off, affecting the service life of the DLC coating.
[0003] In order to solve the peeling problem of DLC coating, it is generally necessary to prepare multiple layers of primer to improve its interface bonding strength when preparing diamond-like coating. For example, one or more of Ti, TiN, TiC, TiCN, Cr, CrN, CrC, CrCN, W, WC and other coatings are used as the primer of diamond-like coating. However, when these materials are used as primer alone, the interface structure is often more chaotic, and the atomic arrangement at the interface is difficult to achieve metallurgical grade bonding, which still causes the DLC coating to be prone to stratification and peeling in the application environment. How to improve the interface bonding strength of DLC coating, reduce the internal stress of DLC coating, and make the coating have both hardness and toughness has always been a difficult problem in the field. Summary of the invention
[0004] The present invention aims at the problems in the prior art and provides a wear-resistant coating with high bonding strength. The present invention solves the problems of high stress and easy peeling of the diamond-like coating by means of a mutually compounded stainless steel substrate layer 1, a Cr base layer 2 and one or more composite coatings 3 arranged in sequence from one side of the stainless steel substrate layer 1 to the outside, thereby obtaining a wear-resistant coating with high bonding strength.
[0005] In the first aspect, the present invention provides a high-bonding wear-resistant coating, comprising a stainless steel substrate layer 1, a Cr primer layer 2 arranged outwardly from one side of the stainless steel substrate layer 1, and one or more composite coatings 3, wherein the composite coating 3 comprises Zr x Al y Cu z Niq Coating layer 31, bonding layer 32, DLC coating 33, wherein 60≤x≤70, 5≤y≤12, 12≤z≤20, 8≤q≤20.
[0006] As a further preferred solution, the composite coating 3 is set to 1-10 groups, the Zr x Al y Cu z Ni q In coating 31, 64≤x≤68, 6≤y≤10, 12≤z≤16, and 9≤q≤16.
[0007] As a further solution, the thickness of the stainless steel substrate 1 is not limited in principle, and technicians can select different thicknesses such as 1 mm, 2 mm, 3 mm, 4 mm, etc. according to needs to achieve different applications.
[0008] As a further solution, the thickness of the Cr base layer 2 is selected from 50-200 nm.
[0009] As a further preferred solution, the thickness of the Cr coating layer 2 is selected from 80-180 nm.
[0010] As a further embodiment, the Zr x Al y Cu z Ni q The thickness of the coating 31 is selected from 50-500 nm.
[0011] As a further preferred solution, the Zr x Al y Cu z Ni q The thickness of the coating 31 is selected from 100-450 nm.
[0012] As a further solution, the thickness of the bonding layer 32 is selected from 1-10 nm.
[0013] As a further preferred solution, the thickness of the bonding layer 32 is selected from 2-8 nm.
[0014] As a further solution, the thickness of the DLC coating 33 is selected from 0.1-5 μm.
[0015] As a further solution, the thickness of the DLC coating 33 is selected from 0.8-4 μm.
[0016] In the second aspect, this solution provides a method for preparing a high-bonding wear-resistant coating, and the preparation method is as follows:
[0017] S1: In a rare-earth atmosphere, the first ion source is turned on to sputter clean the cleaned stainless steel substrate, and then the parameters of the first ion source are adjusted, and the second ion source is turned on to bombard the Cr target. After the bombardment, a first precursor of a high-bonding wear-resistant coating is obtained;
[0018] S2: Using Zr x Al y Cu z Ni q The alloy is used as a target material, the parameters of the first ion source and the second ion source are adjusted respectively, and the first ion source is used to bombard the first precursor of the high-bonding force wear-resistant coating, and the second ion source is used to bombard the target material. After the bombardment, the second precursor of the high-bonding force wear-resistant coating is obtained;
[0019] S3: closing the second ion source and adjusting the parameters of the first ion source to bombard the second precursor of the high-binding force wear-resistant coating to obtain a third precursor of the high-binding force wear-resistant coating;
[0020] S4: Use diamond-like material as the target material, adjust the parameters of the second ion source and bombard the target material, and adjust the parameters of the first ion source at the same time. After the bombardment, a high-bonding and wear-resistant coating with a layer of composite coating 3 is obtained. Repeat steps S2-S4 N times to obtain a high-bonding and wear-resistant coating with N groups of composite coatings 3, where N is greater than or equal to 1.
[0021] As a further preferred solution, in step S1, the inert atmosphere is selected from any one of argon, helium, krypton, and xenon, wherein the gas pressure is selected from 1*10 -2 -5*10 -2 Pa.
[0022] As a further preferred solution, the step of cleaning the substrate in step S1 is: immersing the stainless steel substrate in a cleaning solution and ultrasonically cleaning it for 15-30 minutes, then washing it with deionized water 1-3 times, each time ultrasonically cleaning it for 5-20 minutes, and drying it, and the cleaning is considered complete.
[0023] As a further preferred solution, the cleaning solution is selected from any one of ethanol and acetone.
[0024] As a further preferred solution, when the first ion source is used for sputtering cleaning in step S1, the sputtering energy is 50-100 eV, the current is 5-15 mA, and the sputtering time is 3-10 min.
[0025] As a further preferred solution, in step S1, when bombarding the Cr target, the sputtering energy of the first ion source is 50-200 eV, the current is 6-30 mA, the sputtering energy of the second ion source is 800-1000 eV, the current is 60-90 mA, and the sputtering time is 1-20 min.
[0026] As a further preferred scheme, in step S2, when bombarding the first precursor of the high-bonding wear-resistant coating, the sputtering energy of the first ion source is 50-200eV, the current is 6-30mA, and when bombarding the target material, the sputtering energy of the second ion source is 800-1000eV, the current is 70-90mA, and the sputtering time is 15-60min.
[0027] As a further preferred solution, in step S3, the sputtering energy of the first ion source is 100-400 eV, the current is 10-40 mA, and the sputtering time is 1-5 min.
[0028] As a further preferred solution, in step S4, the material for preparing diamond-like carbon is selected from a high-purity graphite target.
[0029] As a further preferred solution, in step S4, the sputtering energy of the second ion source is 600-900 eV, the current is 50-80 mA, the sputtering time is 30-120 min, and the sputtering energy of the first ion source is 50-200 eV, and the current is 6-30 mA.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] The present invention provides a high-bonding wear-resistant coating, which effectively solves the problem of easy peeling of DLC coating. By setting a Cr base layer on a stainless steel substrate and adding one or more layers of composite coating thereon, the bonding strength between the coating and the substrate is significantly improved. Specifically, the Cr base layer utilizes the good compatibility between stainless steel and Cr metal to provide a stable adhesion basis for subsequent coatings. x Al y Cu z Ni q The coating forms an intermetallic compound with Cr, which effectively resists the stress caused by peeling and temperature changes, further enhancing the bonding strength. x Al y Cu z Ni q The coating is placed on the surface of the DLC layer and a bonding layer is introduced to relieve the internal stress of the DLC coating and prevent cracking. In addition, the design of multiple sets of composite coatings optimizes the wear resistance of the coating, improves the stability of the overall coating, and extends the service life of the coating. This innovative solution provides an effective solution for the application of high-bonding wear-resistant coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 Schematic diagram of the positions of the rotatable target base, sample base, first ion source and second ion source for preparing a high-bonding force wear-resistant coating.
[0034] Figure 2 Schematic diagram of the high-bonding wear-resistant coating prepared in Example 1.
[0035] Among them, 1-stainless steel substrate layer; 2-Cr base layer; 3-composite coating; Zr x Al y Cu z Ni q Coating - 31; 32 - bonding layer; 33 - DLC coating. DETAILED DESCRIPTION
[0036] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0037] In the first aspect, the present invention provides a high-bonding wear-resistant coating, comprising a stainless steel substrate layer 1, a Cr primer layer 2 arranged outwardly from one side of the stainless steel substrate layer 1, and one or more composite coatings 3, wherein the composite coating 3 comprises Zr x Al y Cu z Ni q Coating layer 31, bonding layer 32, DLC coating 33, wherein 60≤x≤70, 5≤y≤12, 12≤z≤20, 8≤q≤20.
[0038] In order to solve the problem that the DLC coating is easy to peel off, the present invention provides a high-bonding wear-resistant coating, by arranging a Cr primer layer 2 on a stainless steel substrate layer 1, and arranging one or more layers of composite coating 3 on the primer layer 2, the bonding force between the DLC coating and the substrate layer is improved, and the problem that the DLC coating is easy to peel off is solved; specifically, the present solution firstly arranges a Cr primer layer 2 on the stainless steel substrate layer 1, and utilizes the good compatibility between stainless steel and Cr metal to improve the bonding force between the coating and the substrate, thereby providing a good adhesion foundation for the subsequent wear-resistant coating, and on this basis, we arrange one or more layers of composite coating 3 on the Cr primer layer 2, wherein in the first layer of composite coating 3 arranged on the Cr primer layer 2, Zr x Aly Cu z Ni q The coating 31 is in direct contact with the Cr base layer 2. We believe that the Zr x Al y Cu z Ni q It may form intermetallic compounds with Cr metal, thus effectively resisting the stress caused by peeling and thermal expansion, and improving the bonding strength between Cr base layer 2 and Zr x Al y Cu z Ni q The bonding strength between the coatings 31 is controlled by x Al y Cu z Ni q The atomic percentage of Zr x Al y Cu z Ni q It has a thermal expansion coefficient close to that of Cr, thus reducing the interface peeling caused by thermal stress during temperature changes. x Al y Cu z Ni q With the cooperation of the coating 31, the present solution effectively improves the bonding force of the composite coating 3 on the Cr base layer 2; in addition, in order to solve the problem of too high internal stress and insufficient toughness of the DLC coating 33, the present solution sets the DLC coating 33 on the Zr x Al y Cu z Ni q On the coating 31, and on the Zr x Al y Cu z Ni q The bonding layer 32 is introduced between the coating 31 and the DLC coating 33. On the one hand, Zr with good hardness, wear resistance, high elastic modulus and toughness x Al y Cu z Ni q The coating 31 helps to fully relieve the internal stress of the DLC coating and prevent the DLC coating from cracking. On the other hand, the existence of the bonding layer 32 comes from the carbon atoms in the Zr x Al y Cu z Ni q Deposition and diffusion in the microscopic defects of the coating 31. The carbon atoms deposited in the microscopic defects can combine with Zr x Al y Cu z Niq Coating 31, in Zr x Al y Cu z Ni q A bonding layer 32 with a nanometer thickness is formed between the coating 31 and the DLC coating 33. The existence of the bonding layer 32 helps to reduce the stress between the two materials and improve the anti-peeling performance of the coating through nano-scale interface bonding, thereby effectively improving the Zr x Al y Cu z Ni q The bonding degree between coating 31 and DLC coating 33 is improved, the bonding force is improved, and the wear resistance of composite coating 3 is optimized to extend the coating life; finally, in order to further improve the stability of high bonding force and wear-resistant coating, relieve the internal stress of DLC coating 33, and avoid cracking, delamination and shedding of coating, the composite coating 3 is set as one or more groups in this scheme. The multiple groups of composite coating 3 here refer to the Zr x Al y Cu z Ni q The coating 31, the bonding layer 32, and the DLC coating 33 are sequentially arranged in multiple groups in a cycle. The composite coating 3 arranged in multiple groups helps to utilize the Zr in the composite coating 3. x Al y Cu z Ni q The interaction effect between the coating 31, the bonding layer 32 and the DLC coating 33 effectively releases stress when subjected to external load impact, thereby effectively preventing cracking and delamination of the coating and fully extending the life of the coating; under the joint action of different coatings, this scheme obtains a wear-resistant coating with high bonding strength.
[0039] As a preferred example of some optional parameters, the composite coating 3 is set to 1-10 groups, the Zr x Al y Cu z Ni q In coating 31, 64≤x≤68, 6≤y≤10, 12≤z≤16, and 9≤q≤16.
[0040] As examples of some optional parameters, the thickness of the stainless steel substrate 1 is not limited in principle, and technicians can select different thicknesses such as 1 mm, 2 mm, 3 mm, 4 mm, etc. according to needs to achieve different applications.
[0041] As examples of some optional parameters, the thickness of the Cr coating layer 2 is selected from 50-200 nm.
[0042] As a preferred example of some optional parameters, the thickness of the Cr base layer 2 is selected from 80-180nm. The thickness of the Cr base layer 2 selected from 80-180nm helps to further enhance the thickness of the Cr base layer 2 and the stainless steel substrate layer 1 and Zr x Al y Cu z Ni q The composite effect between the coatings 31 relieves internal stress at the same time, thereby further optimizing the interface bonding strength between the high bonding strength and wear-resistant coatings.
[0043] As examples of some optional parameters, the Zr x Al y Cu z Ni q The thickness of the coating 31 is selected from 50-500 nm.
[0044] As a preferred example of some optional parameters, the Zr x Al y Cu z Ni q The thickness of the coating 31 is selected from 100-450nm. Under the premise of ensuring the hardness and wear resistance of the coating, when Zr x Al y Cu z Ni q When the thickness of the coating 31 is selected from 100-450nm, it helps to optimize the overall structural strength and toughness of the coating, effectively prevent the coating from cracking and peeling under external stress, and at the same time ensure good bonding between the coating and the Cr base layer 2 and the bonding layer 32.
[0045] As examples of some optional parameters, the thickness of the bonding layer 32 is selected from 1-10 nm.
[0046] As a preferred example of some optional parameters, the thickness of the bonding layer 32 is selected from 2-8 nm. The thickness of the bonding layer 32 selected from 2-8 nm helps to promote Zr x Al y Cu z Ni q The interaction between the coating 31 and the DLC coating 33 provides sufficient contact area, enhances the interfacial adhesion, and avoids the internal stress that may be introduced when the thickness is too large, thereby ensuring the overall toughness and stability of the coating.
[0047] As examples of some optional parameters, the thickness of the DLC coating 33 is selected from 0.1-5 μm.
[0048] As examples of some optional parameters, the thickness of the DLC coating 33 is selected from 0.8-4 μm.
[0049] In a second aspect, the present invention provides a method for preparing a high-bonding wear-resistant coating, such as Figure 1 As shown, the preparation method is as follows:
[0050] S1: In a rare-earth atmosphere, the first ion source is turned on to sputter clean the cleaned stainless steel substrate, and then the parameters of the first ion source are adjusted, and the second ion source is turned on to bombard the Cr target. After the bombardment, a first precursor of a high-bonding wear-resistant coating is obtained;
[0051] S2: Using Zr x Al y Cu z Ni q The alloy is used as a target material, the parameters of the first ion source and the second ion source are adjusted respectively, and the first ion source is used to bombard the first precursor of the high-bonding force wear-resistant coating, and the second ion source is used to bombard the target material. After the bombardment, the second precursor of the high-bonding force wear-resistant coating is obtained;
[0052] S3: closing the second ion source and adjusting the parameters of the first ion source to bombard the second precursor of the high-binding force wear-resistant coating to obtain a third precursor of the high-binding force wear-resistant coating;
[0053] S4: Use diamond-like material as the target material, adjust the parameters of the second ion source and bombard the target material, and adjust the parameters of the first ion source at the same time. After the bombardment, a high-bonding and wear-resistant coating with a layer of composite coating 3 is obtained. Repeat steps S2-S4 N times to obtain a high-bonding and wear-resistant coating with N groups of composite coatings 3, where N is greater than or equal to 1.
[0054] In the process of preparing high-bonding wear-resistant coating, this paper uses high-energy ion beam to deposit Zr x Al y Cu z Ni q The first precursor of the high bonding strength wear-resistant coating of coating 31 is sputtered and etched to generate a large number of microscopic defects on the surface of the deposited amorphous coating. The surface energy of this structure is high and the activity is large. When the DLC coating is subsequently deposited, carbon atoms can enter these defects to build a nano-thick bonding layer, thereby increasing the Zr x Al y Cu z Ni q The bonding force between the coating 31 and the DLC coating 33 is improved, and the hardness and wear resistance of the coating are optimized.
[0055] As a preferred example of some optional parameters, in step S1, the inert atmosphere is selected from any one of argon, helium, krypton, and xenon, wherein the gas pressure is selected from 1*10 -2 -5*10 -2 Pa.
[0056] As a preferred example of some optional parameters, the step of cleaning the substrate in step S1 is: immersing the stainless steel substrate in a cleaning solution and ultrasonically cleaning it for 15-30 minutes, then washing it with deionized water 1-3 times, each time ultrasonically cleaning it for 5-20 minutes, and drying it, and the cleaning is considered complete.
[0057] As a preferred example of some optional parameters, the cleaning solution is selected from any one of ethanol and acetone. Using ethanol or acetone to ultrasonically clean the substrate can effectively remove oil stains on the substrate surface and prevent the surface oil stains from affecting the experimental results.
[0058] As a preferred example of some optional parameters, when the first ion source is used for sputtering cleaning in step S1, the sputtering energy is 50-100 eV, the current is 5-15 mA, and the sputtering time is 3-10 min. Using sputtering cleaning to clean the stainless steel substrate helps to deeply remove the attachments and oxide layer on the surface of the substrate, and activate the surface of the stainless steel substrate, creating a good environment for the subsequent deposition of the Cr base layer 2.
[0059] As preferred examples of some optional parameters, in step S1, when bombarding the Cr target, the sputtering energy of the first ion source is 50-200 eV, the current is 6-30 mA, the sputtering energy of the second ion source is 800-1000 eV, the current is 60-90 mA, and the sputtering time is 1-20 min.
[0060] As a preferred example of some optional parameters, in step S2, when bombarding the first precursor of the high-bonding strength wear-resistant coating, the sputtering energy of the first ion source is 50-200eV, the current is 6-30mA, and when bombarding the target material, the sputtering energy of the second ion source is 800-1000eV, the current is 70-90mA, and the sputtering time is 15-60min.
[0061] As a preferred example of some optional parameters, in step S3, the sputtering energy of the first ion source is 100-400 eV, the current is 10-40 mA, and the sputtering time is 1-5 min.
[0062] As a preferred example of some optional parameters, in step S4, the material for preparing diamond-like carbon is selected from a high-purity graphite target.
[0063] As preferred examples of some optional parameters, in step S4, the sputtering energy of the second ion source is 600-900 eV, the current is 50-80 mA, the sputtering time is 30-120 min, and the sputtering energy of the first ion source is 50-200 eV, and the current is 6-30 mA.
[0064] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0065] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0066] Example 1
[0067] S1: 304 stainless steel with a thickness of 1 mm was used as the substrate. It was first ultrasonically cleaned with alcohol for 15 min, then ultrasonically cleaned twice with deionized water for 15 min each time. After drying, it was installed on the sample base and the vacuum was pumped to 5*10 -4 Pa, filled with argon to 2.8*10 -2 Pa, and set the sample stage speed to 3rpm. Turn on the first ion source, set the sputtering energy to 80eV, the current to 10mA, and sputter for 10min, then adjust the sputtering energy to 50eV, the current to 6mA, and the time to 10min, turn on the second ion source, bombard the Cr target, wherein the second ion source has a sputtering energy of 700eV, a current of 60mA, and a sputtering time of 10min, and obtain the first precursor of the high-bonding wear-resistant coating, wherein the thickness of the Cr bottom layer 2 is 150nm;
[0068] S2: Convert the target to Zr 66 Al8Cu 12 Ni 14 alloy target, the second ion source sputtering energy was adjusted to 800 eV, the current was 70 mA, and the sputtering time was 30 min; at the same time, the first ion source sputtering energy was adjusted to 80 eV, the current was 10 mA, and the sputtering time was 30 min, wherein Zr x Al y Cu z Ni q The coating 31 has a thickness of 120 nm;
[0069] S3: Turn off the second ion source, adjust the sputtering energy of the first ion source to 400 eV, the current to 40 mA, and sputter for 5 min;
[0070] S4: Change the target material to a carbon target, turn on the second ion source, set the sputtering energy of the second ion source to 900eV, the current to 80mA, and sputter for 120min; at the same time, adjust the sputtering energy of the first ion source to 60eV, the current to 7mA, and sputter for 120min. After the sputtering, a high-bonding strength and wear-resistant coating is obtained, wherein the thickness of the bonding layer 32 is 5nm, and the thickness of the DLC coating 33 is 1μm.
[0071] Example 2
[0072] The preparation method and steps are the same as those in Example 1, except that Zr 62 Al 12 Cu 18 Ni8 replaces Zr 66 Al8Cu 12 Ni 14 .
[0073] Example 3
[0074] The preparation method and steps are the same as those in Example 1, except that the thickness of the Cr base layer 2 is 50 nm.
[0075] Example 4
[0076] The preparation method and steps are the same as those in Example 1, except that Zr x Al y Cu z Ni q The coating 31 has a thickness of 50 nm.
[0077] Example 5
[0078] The preparation method and steps are the same as those in Example 1, except that the thickness of the bonding layer 32 is 3 nm.
[0079] Example 6
[0080] The preparation method and steps are the same as those in Example 1, except that the thickness of the DLC coating 33 is selected to be 0.75 μm.
[0081] Example 7
[0082] The preparation method and steps are the same as those in Example 1, except that steps 2-4 are repeated twice to prepare a high-bonding wear-resistant coating having two groups of composite coatings 3.
[0083] Comparative Example 1
[0084] The preparation method and steps are the same as those in Example 1, except that no Cr base layer 2 is provided.
[0085] Comparative Example 2
[0086] The preparation method and steps are the same as those in Example 1, except that Zr 66Al8Cu 12 Ni 14 Coating layer 31 and bonding layer 32.
[0087] Comparative Example 3
[0088] The preparation method and steps are the same as those in Example 1, except that Al is used to replace Cr as the base layer 2.
[0089] Comparative Example 4
[0090] The preparation method and steps are the same as those in Example 1, except that Fe 70 Cr 10 B 20 Replace Zr 66 Al8Cu 12 Ni 14 Coating 31.
[0091] Table 1
[0092]
[0093]
[0094]
[0095] Note: The substrate layer in Table 1 refers to the coating used as the substrate in the high-bonding wear-resistant coating, such as stainless steel substrate layer 1. The primer layer refers to the coating used as the primer for the composite coating in the high-bonding wear-resistant coating, such as Cr primer layer 2. Amorphous alloy is an alloy material with an amorphous structure, such as Zr x Al y Cu z Ni q , 60≤x≤70, 5≤y≤12, 12≤z≤20, 8≤q≤20, Co 66 Fe4Si 15 B 15 .
[0096] Table 2
[0097]
[0098]
[0099] It can be observed from Examples 1-7 and Comparative Examples 1-4 that Examples 1-7 exhibit interface bonding force and friction coefficient far superior to those of Comparative Examples 1-4, indicating that the high bonding force and wear-resistant coating proposed in the present invention can effectively improve the interface bonding force of the DLC coating and reduce the internal stress of the DLC coating, thereby avoiding cracking, delamination, and shedding of the coating and extending the service life of the DLC coating.
[0100] From Example 1 and Comparative Examples 1-2, it can be observed that no matter the Cr base layer 2 is missing or the Zr x Al y Cu z Ni q The interface bonding force and friction coefficient of the coating 31 and the bonding layer 32 of the comparative example 1-2 are seriously affected. This may be because the good interface bonding force in the high bonding wear-resistant coating comes from the Cr base layer 2 and the Zr x Al y Cu z Ni q The mutual compounding effect between the coating 31 and the bonding layer 32, the good compatibility between the Cr base layer 2 and the stainless steel provides a good adhesion basis for the subsequent wear-resistant coating, and the Zr x Al y Cu z Ni q The thermal expansion coefficient of coating 31 is similar to that of Cr base layer, and the construction of intermetallic compounds realizes the Zr x Al y Cu z Ni q The coating 31 is bonded to the Cr base layer, and the presence of the bonding layer 32 can effectively utilize the Zr x Al y Cu z Ni q The coating 31 has good hardness, wear resistance and toughness, while fully relieving the internal stress of the DLC coating and preventing the DLC coating from cracking. x Al y Cu z Ni q The coating 31 and the bonding layer 32 are both essential for high bonding strength and wear-resistant coating. Example 1 and Comparative Examples 3-4 also prove this conclusion. It can be observed that whether Ti is used to replace Cr in the Cr base layer 2 or Co is used 66 Fe4Si 15 B 15 Replace Zr x Al y Cu z Ni q Zr in coating 31 66 Al8Cu 12 Ni 14 , Comparative Examples 3-4 failed to fully exert their due effects, indicating that the high-bonding wear-resistant coating proposed in the present invention exhibits good bonding strength and friction coefficient from the Cr base layer 2, Zr x Al y Cu z Ni qThe coating layer 31 , the bonding layer 32 and the DLC coating layer 33 are compounded with each other.
[0101] Zr x Al y Cu z Ni q Different atomic percentages in Zr will affect x Al y Cu z Ni q In terms of hardness, corrosion resistance, toughness, and elastic modulus, it can be observed from Examples 1-2 that, compared with Example 2, Example 1, which satisfies the atomic percentage range of 64≤x≤68, 6≤y≤10, 12≤z≤16, and 9≤q≤16, has a higher interface bonding force and a better friction coefficient, indicating that when Zr x Al y Cu z Ni q When the atomic percentage satisfies 64≤x≤68, 6≤y≤10, 12≤z≤16, 9≤q≤16, Zr x Al y Cu z Ni q The alloy may have better toughness and elastic modulus, and can better exert the compounding effect with the Cr base layer 2 and the bonding layer 32, thereby improving the performance of Example 1.
[0102] It can be observed in Examples 1 and 3-6 that different coating thicknesses in the high-bonding wear-resistant coating are also one of the factors affecting the interfacial bonding force and friction coefficient of the high-bonding wear-resistant coating. It can be observed that, compared with Examples 3-6, when the thickness of the Cr base layer 2 is selected from 80-180 nm, the Zr x Al y Cu z Ni q When the thickness of coating 31 is selected from 100-450nm, the thickness of bonding layer 32 is selected from 2-8nm, and the thickness of DLC coating 33 is selected from 0.5-4μm, Example 1 shows better interface bonding force and friction coefficient. This may be because when different coatings meet the above layer thicknesses, it helps to fully exert the compounding effect between different layers while fully alleviating internal stress, thereby further improving the bonding ability between different layers.
[0103] It can be observed in Examples 1 and 7 that both Examples 1 and 7 exhibit good interface bonding force and friction coefficient, indicating that the arrangement of one or more sets of composite coatings 3 evenly exerts good interface bonding ability and avoids the occurrence of peeling and cracking.
[0104] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A high-bonding wear-resistant coating, characterized in that: The invention comprises a stainless steel substrate layer (1), a Cr base layer (2) arranged outward from one side of the stainless steel substrate layer (1), and one or more groups of composite coatings (3), wherein the composite coating (3) comprises, outward from the Cr base layer (2), Zr x Al y Cu z Ni q A coating (31), a bonding layer (32), and a DLC coating (33), wherein 60≤x≤70, 5≤y≤12, 12≤z≤20, and 8≤q≤20.
2. The high-bonding wear-resistant coating according to claim 1, characterized in that: The composite coating (3) is arranged in 1-10 groups, the Zr x Al y Cu z Ni q In the coating (31), 64≤x≤68, 6≤y≤10, 12≤z≤16, and 9≤q≤16.
3. The high-bonding wear-resistant coating according to claim 1, characterized in that: The thickness of the Cr base layer (2) is selected from 50-200 nm; Preferably, the thickness of the Cr base layer (2) is selected from 80-180 nm; Preferably, the Zr x Al y Cu z Ni q The coating (31) has a thickness selected from 50-500 nm; Preferably, the Zr x Al y Cu z Ni q The thickness of the coating (31) is selected from 100-450 nm.
4. The high-bonding wear-resistant coating according to claim 1, characterized in that: The thickness of the bonding layer (32) is selected from 1-10 nm; Preferably, the thickness of the bonding layer (32) is selected from 2-8 nm; Preferably, the thickness of the DLC coating (33) is selected from 0.1-5 μm; Preferably, the thickness of the DLC coating (33) is selected from 0.8-4 μm.
5. A method for preparing a high-bonding wear-resistant coating, characterized in that: The steps include: S1: In a rare-earth atmosphere, the first ion source is turned on to sputter clean the cleaned stainless steel substrate, and then the parameters of the first ion source are adjusted, and the second ion source is turned on to bombard the Cr target. After the bombardment, a first precursor of a high-bonding wear-resistant coating is obtained; S2: Using Zr x Al y Cu z Ni q The alloy is used as a target material, the parameters of the first ion source and the second ion source are adjusted respectively, and the first ion source is used to bombard the first precursor of the high-bonding force wear-resistant coating, and the second ion source is used to bombard the target material. After the bombardment, the second precursor of the high-bonding force wear-resistant coating is obtained; S3: closing the second ion source and adjusting the parameters of the first ion source to bombard the second precursor of the high-binding force wear-resistant coating to obtain a third precursor of the high-binding force wear-resistant coating; S4: using diamond-like carbon material as a target material, adjusting the parameters of the second ion source and bombarding the target material, and adjusting the parameters of the first ion source at the same time, after the bombardment, obtaining a high-bonding wear-resistant coating having a layer of composite coating (3), repeating steps S2-S4 N times, obtaining a high-bonding wear-resistant coating having N groups of composite coatings (3), wherein N is greater than or equal to 1.
6. The method for preparing a high-bonding wear-resistant coating according to claim 5, characterized in that: In step S1, the inert atmosphere is selected from any one of argon, helium, krypton, and xenon, wherein the pressure is selected from 1*10 -2 -5*10 -2 Pa; The step of cleaning the substrate in step S1 is: immersing the stainless steel substrate in a cleaning solution and ultrasonically cleaning it for 15-30 minutes, then washing it with deionized water for 1-3 times, ultrasonically cleaning it for 5-20 minutes each time, and drying it; The cleaning solution is selected from any one of ethanol and acetone; When the first ion source is used for sputtering cleaning in step S1, the sputtering energy is 50-100 eV, the current is 5-15 mA, and the sputtering time is 3-10 min.
7. The method for preparing a high-bonding wear-resistant coating according to claim 5, characterized in that: In the step S1, when bombarding the Cr target, the sputtering energy of the first ion source is 50-200 eV, the current is 6-30 mA, the sputtering energy of the second ion source is 800-1000 eV, the current is 60-90 mA, and the sputtering time is 1-20 min.
8. The method for preparing a high-bonding wear-resistant coating according to claim 5, characterized in that: In step S2, when bombarding the first precursor of the high-bonding wear-resistant coating, the sputtering energy of the first ion source is 50-200eV, the current is 6-30mA, and when bombarding the target material, the sputtering energy of the second ion source is 800-1000eV, the current is 70-90mA, and the sputtering time is 15-60min.
9. The method for preparing a high-bonding wear-resistant coating according to claim 5, characterized in that: In step S3, the sputtering energy of the first ion source is 100-400 eV, the current is 10-40 mA, and the sputtering time is 1-5 min.
10. The method for preparing a high-bonding wear-resistant coating according to claim 5, characterized in that: In the step S4, the material for preparing diamond-like carbon is selected from a high-purity graphite target; In step S4, the sputtering energy of the second ion source is 600-900 eV, the current is 50-80 mA, and the sputtering time is 30-120 min. The sputtering energy of the first ion source is 50-200 eV, and the current is 6-30 mA.